2016
DOI: 10.1177/0194599815627786
|View full text |Cite
|
Sign up to set email alerts
|

Acute Invasive Fungal Rhinosinusitis

Abstract: This series represents one of the largest single-institution experiences of AIFRS published to date. Timely diagnosis is necessary to improve patient outcomes and limit morbidity. Maintaining a high index of suspicion in at-risk patient populations, followed by prompt evaluation and management, is crucial in suspected AIFRS. The presence or absence of certain findings appear to correlate with biopsy results and may aid in appropriately gauging clinical suspicion for the presence of AIFRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 13 publications
5
47
0
Order By: Relevance
“…By using the bilateral mean model, we demonstrated that Mucor induced AIFR is associated with higher prevalence of bilateral findings. Similar to prior studies evaluating patients with AIFR, facial soft tissue thickening and orbital involvement were not common features 4 , 25 . Mucosal thickening in the sinuses was a common feature both in Mucor and Aspergillus AIFR as has been previously reported 18 , 20 , 26 .…”
Section: Discussionsupporting
confidence: 84%
“…By using the bilateral mean model, we demonstrated that Mucor induced AIFR is associated with higher prevalence of bilateral findings. Similar to prior studies evaluating patients with AIFR, facial soft tissue thickening and orbital involvement were not common features 4 , 25 . Mucosal thickening in the sinuses was a common feature both in Mucor and Aspergillus AIFR as has been previously reported 18 , 20 , 26 .…”
Section: Discussionsupporting
confidence: 84%
“…Actually, as we observed in our current cohort, a significant percentage of patients with confirmed AIFRS (39.5%) had CT scans with few or even normal findings. Our data reinforce that nasal endoscopy must be elected as the preferred choice to evaluate patients at risk because it can reveal subtle changes in the nasal mucosa [6, 14, 15] that are not detected by imaging exams [6, 15]. Taking into consideration only CT scans findings, these patients would have experienced a delayed treatment, and this could negatively impact on their outcome.…”
Section: Discussionsupporting
confidence: 56%
“…The early diagnosis of AIFRS is challenging and demands accurate and fast tests [14]. With this aim, we have established a protocol to maximize the sensitivity to diagnose AIFRS, in such a way that patients under risk, with subtle or even with non-specific symptoms, are immediately referred by hematologists to ENT evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, the most commonly affected region was the paranasal sinuses (eight patients, 100%), followed by the orbit (three patients, 37.5%), brain (two patients, 25%), and lung (two patients, 25%). Payne et al[20] studied 41 cases of acute invasive fungal sinusitis and found that mucosal abnormalities of the middle turbinate and septum, specifically necrosis of the middle turbinate, could be important predictors of disease. Among eight patients, there were six with Cunninghamella infection confirmed by culture/biopsy from the nasal cavity, one with Cunninghamella infection confirmed by culture of the sputum, and one (our patient) with Cunninghamella infection confirmed by culture of the eye canthus secretions.…”
Section: Discussionmentioning
confidence: 99%